Surat Jerami di Meja Austin: Penggunaan Speech Act Theory Sebagai Usaha Pembacaan Efektif Ujaran Performatif dalam Surat Yakobus (Indonesian Journal of Theology, 2016)
Many hermeneutical approaches have been developed in response to interpretive difficulties arising from the reading of text, especially sacred writings. The linguistic ontology developed by John Langshaw Austin (1911-1960) might offer a novel perspective for “reading” such an utterance. For Austin, there are multiple kinds of speech effected in the instance of human uttering. A given action therefore results out of a person’s given speech. Austin terms “performative utterance” that action performed by way of speech. Further explicating his speech-act theory, Austin outlines that the action exemplified by a given speech are, in fact, three simultaneous acts—first the “locutionary act,” as the compilation of the particular words uttered; next the “illocutionary act,” as the force rendered by this given speech; then the “perlocutionary act,” as the effect consequentially achieved upon a speech’s audience. By proposing that Austin’s approach be deployed to interpret the Epistle of James, I consider a number of ways in which such an interpretation would be demonstrably enriched via speech-act theory. I contend that an interpreter of James’ letter must distinguish among the three kinds of acts being performed in the work of the epistolary author. The culminating aim, then, is to discern what outcomes might have been intended by the epistolary author, in relation to the letter’s original audience.